Development of a WDM platform for charged-particle stopping experiments. (May 2016) - Zylstra, A B; Frenje, J A; Grabowski, P E; Li, C K; Collins, G W; Fitzsimmons, P; Glenzer, S; Graziani, F; Hansen, S B; Hu, S X; Johnson, M Gatu; Keiter, P; et al.
Abstract: A platform has been developed for generating large and relatively quiescent plasmas in the warm-dense matter (WDM) regime on the OMEGA laser facility. A cylindrical geometry is used to allow charged-particle probing along the axis. The plasma heating is radiative by L-shell emission generated on the outside of the cylinder. The cylinder drive is characterized with x-ray diagnostics. Possibilities for direct characterization of the plasma temperature are discussed. Finally, the unimportance of electromagnetic fields around the target is demonstrated with proton radiography. We expect this platform to be used extensively in future experiments studying charged-particle stopping in this regime.